Characterization of allelic variation in the babesia bovis merozoite surface antigen 1 (MSA-1) locus and identification of a cross-reactive inhibition-sensitive msa-1 epitope - Suarez, Carlos E. (2000)
The Babesia bovis merozoite surface antigen 1 (MSA-1), a member of the variable merozoite surface antigen (VMSA) family, is an immunodominant glycoprotein which elicits antibodies that inhibit erythrocyte invasion. While antigenic polymorphism is a general feature of vmsa genes, the molecular basis and extent of msa-1 sequence polymorphism have not been well characterized. In this study we defined the msa-1 locus in the biologically cloned Mexico Mo7 strain of B. bovis and identified the sequence differences between MSA-1 antigenically dissimilar strains. We then determined whether sequences conserved between distinct msa-1 alleles would induce cross-reactive CD4+ T lymphocytes or inhibitory antibodies. The msa-1 locus in Mo7 contains a single msa-1 gene flanked by transcribed genes with no sequence homology to members of the VMSA gene family. Argentina B. bovis strains R1A and S2P have msa-1 genes with amino acid sequences that are 98.8% identical to each other, and antibodies against S2P MSA-1 cross-react with native R1A MSA-1. In contrast, identity between the Argentina and Mexico Mo7 msa-1 alleles is only 52%, with no continuous stretch of identity longer than 16 amino acids. Despite limited sequence conservation, antibodies against R1A MSA-1 were able to inhibit invasion of erythrocytes by Mo7 merozoites. The results indicate that inhibition-sensitive epitopes are conserved despite significant sequence divergence between Mexico and Argentina strain alleles and support a conserved functional role for polymorphic MSA-1 in erythrocyte invasion.